SOSIALISASI RESPON TIME PERAWAT DI RUANG IGD RSUD KARAWANG - Serly, Serly; Dina Hartini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Emergency Room from the beginning to provide fast service to arrivals until they receive services known as response time. Service that is fast, responsive and able to save emergencies is one form of achievement of service quality indicators. This review aims to explain the relationship between response time and patient satisfaction in the Emergency Room. Methods: The research design was a literature review. The database uses Google Scholar, PubMed, Elsevier with the PEOS framework approach. Six published articles 2018-2021 according to the Criteria. Results: five of the six articles stated that the response time for emergency services was fast response and the number of participants who were satisfied with the services of nurses during an emergency was also known. Analysis: slow response time with free time while fast response time with increased satisfaction where fast response time has implications for 5-8 times increasing patient satisfaction in emergency installations. Discussion: the emergency service system at the hospital must determine the evaluation based on the level. Therefore, it is necessary to periodically conduct and improve training for nurses in emergency efforts and for agencies it is expected to optimize the provision of emergency facilities